2021
DOI: 10.1007/s12144-021-01501-4
|View full text |Cite
|
Sign up to set email alerts
|

Does interpersonal sensitivity and paranoid ideation predict nomophobia: an analysis with a young adult sample

Abstract: Nomophobia has been studied extensively due to its negative effects on human health and psychology. In terms of clinical psychology, nomophobia has been linked consistently to depression and anxiety. Studies also investigated whether it is a dependency, an impulse control problem, an obsession or a phobia; however, no clear clinical representation was confirmed. Although it was proposed to be added as an official diagnosis to DSM-5, these attempts were inconclusive. In this study, nomophobia was examined clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
4
5
0
Order By: Relevance
“…However, staff participants cited the fear of losing online friends as a leading cause of overusing smartphones among students. These findings correspond with the findings of previous studies which concluded that social pressure [ 72 , 73 , 74 ] and fear of losing a connection [ 75 , 76 ] were triggers for smartphone addiction. For instance, a study conducted among 2820 Spanish smartphone users found that higher levels of social pressure were associated with higher levels of smartphone addiction [ 73 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, staff participants cited the fear of losing online friends as a leading cause of overusing smartphones among students. These findings correspond with the findings of previous studies which concluded that social pressure [ 72 , 73 , 74 ] and fear of losing a connection [ 75 , 76 ] were triggers for smartphone addiction. For instance, a study conducted among 2820 Spanish smartphone users found that higher levels of social pressure were associated with higher levels of smartphone addiction [ 73 ].…”
Section: Discussionsupporting
confidence: 92%
“…As individuals' fear of missing out on updates increases, the fear they feel when they are away from their smartphones also increases. This finding is parallel to the results of the previous studies in the literature (Yılmaz & Bekaroğlu, 2021). In a study conducted by Shiva et al (2020), a high-level positive relationship is reported between FoMO and nomophobia.…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 89%
“…Interpersonal sensitivity plays an important role in human mental health, and it has some negative impact on individual mental health and social adaptive functions ( 44 ). Additionally, it is also a susceptibility factor for many mental disorders such as depression, anxiety, paranoia, and compulsion ( 45 , 46 ). Thus, obsessive-compulsiveness and interpersonal sensitivity are negligible mental health problems among medical students.…”
Section: Discussionmentioning
confidence: 99%